Disconnection of Ventriculoperitoneal Shunt after Mild Injury over the Catheter's Pathway: Two Cases - Claudia Marcela Restrepo Lugo; Miguel Ángel Maldonado Morán; Andreina Martinez Amado; Luis Rojas; Erik Muñoz; Juan Carlos Luque (Indian Journal of Neurosurgery)
Hydrocephalus is present in 1 of every 1,000 newborns treated with ventriculoperitoneal shunts (VPSs) in the majority of cases. This procedure carries a high risk of complications. One of them is the mechanical disconnection of the system that leads to dysfunction of the shunt and implies neurologic changes that the neurosurgeon has to address as soon as possible. We present two cases of congenital hydrocephalus previously treated with ventriculoperitoneal shunts. The first patient was hit on the right side of his neck. The day after the event, the patient was hypoactive and unable to communicate properly with the examiner and his parents. The radiological cervical X-ray showed disconnection of the catheter at the cervical level. The second case was of a 37-year-old man with hydrocephalus managed with VPS for the first time at the age of 14 years, who was brought to emergency due to rapid onset of symptoms apparently associated with trauma related to a blow with a soccer ball; the patient's X-ray showed fracture of the catheter's path at the thoracic level. For both cases, surgical repair was needed. Results were good, and the patients showed rapid neurologic improvement.